2014
DOI: 10.2478/jtes-2014-0012
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Facility with Evidence-Based Classroom Management Practices: An Investigation of Teachers’ Preparation Programmes and In-service Conditions

Abstract: In the present investigation, teachers’ self-reported knowledge and competency ratings for the evidence-based classroom management practices were analysed. Teachers also reflected on how they learned evidence-based classroom management practices. Results suggest that teachers working in schools that implement Positive Behavioural Interventions and Supports (PBIS) had significantly higher mean knowledge ratings in the area of posting, teaching, reviewing, monitoring and reinforcing expectations than those who d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
9
0
2
Order By: Relevance
“…Teachers who worked in schools that implement Positive Behavioral Interventions and Supports (PBIS) had better performance rating in posting, teaching, reviewing, monitoring, and reinforcing expectations than those who did not. Additionally, teachers with exclusive education license were a better performer in maximizing structure, using different strategies and techniques in classroom management than those who were not [37].…”
Section: High-performance Work Systems Directly and Indirectly Influmentioning
confidence: 98%
“…Teachers who worked in schools that implement Positive Behavioral Interventions and Supports (PBIS) had better performance rating in posting, teaching, reviewing, monitoring, and reinforcing expectations than those who did not. Additionally, teachers with exclusive education license were a better performer in maximizing structure, using different strategies and techniques in classroom management than those who were not [37].…”
Section: High-performance Work Systems Directly and Indirectly Influmentioning
confidence: 98%
“…Research by Feuerborn and colleagues also suggests that teachers in schools implementing SWPBS are more likely to take a preventative approach and show more commitment to positive behaviour support practices (Feuerborn & Chinn, 2012;Feuerborn & Tyre, 2016). In the study of teachers in New York State previously mentioned (Ficarra & Quinn, 2014), teachers working in SWPBS schools reported higher knowledge of establishing, teaching, and reinforcing expectations, which perhaps reflects the strong emphasis on teaching and reinforcement within the SWPBS framework. By comparison, low rates of praise and opportunities to respond were observed in primary classrooms implementing SWPBS with high fidelity (Reinke et al, 2013).…”
Section: Swpbs and Classroom Management Usamentioning
confidence: 92%
“…Several studies investigating teacher use of classroom management practices have been undertaken in the USA. Ficarra and Quinn (2014) asked teachers from all school sectors in the state of New York to rate their knowledge and competency in relation to a number of evidence-based classroom management practices. Overall, teachers reported medium-to-high knowledge and competency ratings for the majority of practices.…”
Section: Teacher Practice Usamentioning
confidence: 99%
“…In the study, 53.3% of the respondents believe that communication skills are worked on sufficiently, 80% believe that these skills are not acquired. Similarly, Ficarra and Quinn (2014) have indicated that teachers have identified classroom management as an area for which they need additional on-site training that will establish or further develop skills not sufficiently addressed in pre-service programmes. According to Kuurme and Carlsson (2010), a routine hierarchical working system and bad relations diminish the quality of school life.…”
Section: Discussionmentioning
confidence: 99%